Cold Injury and Flash Flood Damage in Boro Rice Cultivation in Bangladesh: A Review - Rashid, MM; Yasmeen, R (Bangladesh Rice Journal, 2018)
Increasing population with decreasing resources and increasing climate vulnerability appeared as the great challenges to sustain food security of Bangladesh. Cold stress adversely affects growth and productivity of rice (Oryza sativa L.). Systematic studies have been carried out to improve understanding on rice cold tolerance. Two adverse conditions, such as low temperature stress at reproductive stages and flash flood at maturity affect the Boro rice in the haor areas of Bangladesh. Any deviation of these two phenomena is enough to cause disaster in haor areas. Here, we summarized different types of cold injury, rice cold injury scenario and cold tolerant rice varieties/genotypes available in different countries. Moreover, we discussed on rice cold tolerant barrier and flash flood risk in Boro rice cultivation at haor areas of Bangladesh. Based on the authors’ own research and available data, the concept of overcoming cold and flash flood damage was proposed. According to this concept there were distinguished possible ways how to improve cold tolerance and flash flood problem in Boro rice cultivation in Bangladesh Bangladesh Rice j. 2017, 21(1): 13-25